Hydrodynamics at a microtidal inlet: Analysis of propagation of the main wave components. (5th April 2020) - Melito, Lorenzo; Postacchini, Matteo; Sheremet, Alex; Calantoni, Joseph; Zitti, Gianluca; Darvini, Giovanna; Penna, Pierluigi; Brocchini, Maurizio
Abstract: The evolution of different wave components as they propagate within a microtidal inlet during a storm occurring from 24–26 January 2014 is analysed, in order to improve knowledge on how microtidal river mouths typical of the Adriatic Sea behave. For the first time, the "low-pass filter" mechanism previously ascertained at several macrotidal oceanic inlets around the world has been observed in the field with remarkably specific hydrodynamic conditions, i.e. low tide excursion, permanent connection with the sea and generally milder wave climate than in the ocean. Sea/swell (SS) waves were strongly dissipated before entering the river mouth, through the combined action of wave breaking due to reducing depths and opposing river currents enhanced by rainfall. Infragravity (IG) waves propagated upstream and significant IG wave heights of up to 0.4 m, about 13% of the local water depth, have been observed 400 m upriver (about 10 times the local SS peak wavelength) during storm climax. The IG wave energy here represented over 4% of the maximum offshore storm energy. IG wave components travelled upriver at estimated velocities between 3.6 m/s and 5.5 m/s (comparable with speeds of nonlinear long waves) during intense storm stages up to 600 m into the river channel (about 15 times the local SS peak wavelength), and are enhanced by tide-induced increase in water depths. It is estimated that tide-induced excursion accounted for about 80% of the total mean water elevation at storm peak at about 400 m into the river. Finally, tidal oscillations are detected up to 1.5 km upstream (about 40 times the local SS peak wavelength). This study highlights the dominance of astronomical tide over both wave setup and storm surge in controlling the upriver propagation of IG waves, even in a microtidal environment. Highlights: The evolution of storm waves in a microtidal Mediterranean estuary is analysed. A wave low-pass filtering occurs also with low tide excursion. Tidal excursion accounts for about 80% of total mean water elevation at storm peak. Upriver IG propagation is largely controlled by tide even in microtidal environments.